Disposal-based scarcity: How overstock reduction methods influence consumer brand perceptions and evaluations - Nguyen, Oanh Dinh Yen; Bucic, Tania; Ngo, Liem Viet; Oppewal, Harmen (Journal of the Academy of Marketing Science, 2023)
AbstractOverstock reduction methods offer important marketing signals that may affect consumer brand perceptions. In particular, some overstock reduction methods create disposal-based scarcity, that is, product scarcity resulting from reductions of unsold stock. Three experimental studies reveal distinct effects of incineration, which completely destroys the product, compared with methods that are less destructive, such as recycling, donating, or discounting through factory outlets. Achieving disposal scarcity through destruction ultimately damages consumer brand evaluations. In contrast, recycling, donating, and discounting methods, along with indicating a lack of brand overstock, can enhance brand evaluations. Communicating sold-out stock does not translate into such beneficial effects. These varied effects of different overstock reduction methods are mediated by perceptions of exclusivity, popularity, and wastefulness. Furthermore, the mediating effect of perceived wastefulness in the link between overstock reduction methods and brand evaluations is moderated by self–brand connection but not by perceived brand luxuriousness. This article thus integrates literature on scarcity, branding, wastefulness, and disposal behavior to identify a distinct type of scarcity and the conditions in which it has more positive or negative effects on brand perceptions and evaluations.